2011
DOI: 10.1111/j.1472-8206.2011.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions associated with the use of NSAIDs: a case/noncase analysis of spontaneous reports from the French pharmacovigilance database 2002–2006

Abstract: To evaluate the safety profile of eight oral nonsteroidal anti-inflammatory drugs (NSAIDs) available in France, using data reported through the French pharmacovigilance system. Data (from 2002 to 2006) were analysed for aceclofenac, diclofenac, ketoprofen, meloxicam, naproxen, nimesulide, piroxicam and tenoxicam, focusing on the reported rates of serious adverse drug reactions (ADRs) in the following system organ classes: gastrointestinal, hepatic, cutaneous, renal and cardiovascular. A total of 42 389 serious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 21 publications
1
33
0
8
Order By: Relevance
“…Seven studies (Arvind et al 2004;Hosie et al 1996;Lafrance and Miller 2012;Lapeyre-Mestre et al 2013;Schneider et al 2006;Shi et al 2004;Winkelmayer et al 2008) were found reporting meloxicam exposure of any duration and its effect on renal system (Table 3). Meloxicam was found with no increase in renal risk OR 0 , neither did ibuprofen.…”
Section: Renal Outcomesmentioning
confidence: 94%
See 1 more Smart Citation
“…Seven studies (Arvind et al 2004;Hosie et al 1996;Lafrance and Miller 2012;Lapeyre-Mestre et al 2013;Schneider et al 2006;Shi et al 2004;Winkelmayer et al 2008) were found reporting meloxicam exposure of any duration and its effect on renal system (Table 3). Meloxicam was found with no increase in renal risk OR 0 , neither did ibuprofen.…”
Section: Renal Outcomesmentioning
confidence: 94%
“…They were combined to calculate the risk estimates (OR 0 ). All of the 19 studies (Arvind et al 2004;Biere-Rafi et al 2011;Chang et al 2010;Garcia Rodriguez et al 2008;Hosie et al 1996;Huerta et al 2005;Jick 2000;Lafrance and Miller 2012;Lapeyre-Mestre et al 2013;Layton et al 2003a, b;Mangoni et al 2010a, b;Schneider et al 2006;Shi et al 2004;Singh et al 2004;van Staa et al 2008;Varga et al 2013;Winkelmayer et al 2008) included in our review were adjusted for common variables such as age, sex, comorbidities and concomitant medication, other variables were also recorded here as study characteristics (Tables 1 and 2).…”
Section: Analysis and Outcome Measuresmentioning
confidence: 99%
“…[17] The concomitant use of more than one NSAID has no therapeutic benefits rather, increases the profile of toxicities on the Central Nervous System (CNS) hematologic, renal, and hepatic and respiratory systems. [22][23][24][25][26] Morethan half of shop attendants, 63.2% routinely included Prednisolone 5mg in the single dose combo. This is of serious concern as the risk of gastrointestinal erosion and hemorrhage increases even further with the concomitant use of NSAIDs and corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…[18]. Оценено 38 502 серьезных побоч-ных эффекта со стороны ЖКТ, печени, почек, кожных по-кровов и сердечно-сосудистой системы.…”
unclassified